Microbial Transglutaminase Is Immunogenic and Potentially Pathogenic in Pediatric Celiac Disease - Torsten, Matthias; Aaron, Lerner (Frontiers in Pediatrics, 2018)
The enzyme microbial transglutaminase is heavily used in the food processing industries to ameliorate food qualities and elongate the products’ shelf life. As a protein’s glue, it cross-links gliadin peptides, creating neo-complexes that are immunogenic and potentially pathogenic to celiac disease communities. Even lacking sequence identity, it imitates functionally the endogenous tissue transglutaminase, known to be the autoantigen of celiac disease and representing an undisputable key player in celiac disease initiation and progress. The present mini review expend on the enzyme characteristics, exogenous intestinal sources, its cross-linking capacity to gluten or gliadin, turning naïve protein to immunogenic ones. The current observations on its potential pathogenicity and risks for celiac disease induction are highlighted. Warnings on its potential risks for the gluten dependent conditions are reviewed. When substantiated, it might represent a new environmental factor of celiac disease genesis. The reviewed background might affect nutritional product labeling, impact processed food additive policies and warn the consumers on its health hazards.